An analysis of pronunciation learning strategies of rural Malay ESL learners - Nur Hazwani Hanafi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 2012)
Pronunciation is an important aspect of language that needs to be taught in classroom, yet this aspect of language is often given little attention and it is one of the most difficult problems to be handled. Therefore, there is a need for the students to find their own pronunciation learning strategies so that they will be able to help themselves in learning correct pronunciation that leads to an intelligible and comprehensible communication. The objective of this study was to identify pronunciation learning strategies reportedly used by ESL learners and to observe if ten selected strategies were used in spontaneous pronunciation. The data were collected reportedly using a set of pronunciation learning strategies questionnaires, observation and an interview with pronunciation samples elicited from a group of thirty-four Form four ESL learners. Results from the questionnaire data showed that learners from rural areas tend to avoid using the target language in terms of pronouncing or speaking. This conclusion was made based on high percentages of the students who preferred the input-pronunciation strategies compared to the output-pronunciation strategies. The observation data showed that the students actually used a number of outputpronunciation strategies, for example, “I speak and read slower” and “immediate selfcorrection” to complete the tasks given to them. However, “willing to guess” (inputpronunciation strategy) is still the most used strategy. The interview results showed that the students did agree that they mostly used “guessing” strategies (inputpronunciation strategies) in obtaining new information. The researcher found that there was no discrepancy between the strategies reportedly used by the students and their actual use of the pronunciation strategies in the given pronunciation tasks. The low percentages of output-pronunciation learning strategies usage compared to inputpronunciation strategies are worrying since this could mean that the students are not able to speak in the target language correctly.